Kinetic Studies and Mechanism on the Permanganic Oxidation of L-Lysine in Strong Acid Medium - Iloukhani, H.; rashidi, N.; Moghdasi, M. (Asian Journal of Chemistry, 2012)
Kinetics and mechanism of manganese(VII) oxidation of L-lysine have been studied in aqueous sulfuric acid medium. Various hypotheses for the mechanism of acid catalysis have been tested and it has been found that arte is related to the activity of water in accordance with Bunnett’s hypothesis. The energy and entropy to activation and frequency factor have been caloculated usimg the Eyring and Aeeheniuus plots. Mechanisms in agreement with the observations are reported. The experimental rate law for the reaction was found to be -d[Mn(VII)] / dt = k0[L – Lysine][Mn(VII)] The reaction appears to involve an acid catalysis and the data showed the role of water molecules in the rate-determinig step facilitating proton transfer which satisfies Bunnett’s theory.